Management of intracardiac thrombosis in newborns: a case series and a narrative review of the literature - De Rose, Domenico Umberto; Mecarini, Federico; Campanale, Cosimo Marco; Pugnaloni, Flaminia; Passarella, Chiara; Secinaro, Aurelio; Bracaglia, Giorgio; Luciani, Matteo; Toscano, Alessandra; Capolupo, Irma; Dotta, Andrea (Frontiers in Cardiovascular Medicine, 2025)
BackgroundNeonatal intracardiac thrombosis (ICT) is an uncommon but increasingly recognized condition that impacts neonatal morbidity and mortality, especially in critically ill term and preterm infants. Management includes supportive care and pharmacological or surgical intervention. This study explores the challenges associated with ICT in neonates.MethodsWe described the clinical presentation and multidisciplinary management of two cases of intracardiac thrombosis. We also reviewed literature from Medline and PubMed using MeSH terms (“intracardiac thrombosis” AND “newborn”).Case seriesIn the first case, a very early (day 1) atrial thrombosis was unusually attached at the fossa ovalis and floating between the right and left atrium in an early-term newborn with meconium-aspiration syndrome and fetal inflammatory response syndrome. In the second case, a late-preterm neonate developed a left atrial thrombus after resuscitation at birth, with severe anemia (hemoglobin 5 g/dl) requiring two blood transfusions. In both cases, treatment with low-molecular-weight heparin resolved the thrombus without complications.ResultsCritically ill term and preterm neonates should be carefully monitored due to the increased risk of thromboembolic events. The timing and decision to treat ICTs remain challenging. Supportive therapy is always indicated, including treatment of conditions such as sepsis, dehydration, anemia, and coagulopathy. Anticoagulant therapy with low-molecular-weight heparin (LMWH) offers a favorable risk/benefit ratio, except in neonates at high hemorrhagic risk.ConclusionNeonatal intracardiac thrombosis, though rare, requires high clinical suspicion and prompt multidisciplinary management. Early diagnosis and individualized anticoagulant therapy can lead to favorable outcomes while minimizing complications.